Application of Discovery Learning Model in Mathematics Learning to Determine Students’ Mathematical Communication Ability - Hariyo Sugeng Widodo; Marhan Taufik; Reni Dwi Susanti (Mathematics Education Journal, 2021)
This research aimed to describe the application of the discovery learning model in mathematics learning and to describe students' mathematical communication skills both orally and in writing. The approach to this research is a qualitative approach, while the type of research used is descriptive. This research was conducted with the subject of class VIII C students in the 2019/2020 school year. The data collection techniques used in this study were observation to determine students 'mathematical communication skills orally and tests to determine students' written communication skills. The instruments used in this study were the observation sheet of students' communication skills and the test in the form of description questions. Based on the results obtained, it shows that the application of the discovery learning model in this study can be said to be quite good but the results are less than optimal and there are several obstacles experienced during learning activities using the discovery learning model. Meanwhile, the level of students' mathematical communication skills is quite good with a percentage of 56% for oral and 59.48% for written.